A Study for the Improvement of the Energy Performance Certificate (EPC) System in Turkey - Yilmaz, Didem Gunes; Cesur, Fatma (Mdpi, 2023)
This study aims to examine the current status of Turkey's energy consumption and energy performance system and draw improvements. To this aim, this study adopted a qualitative research method. A literature review was conducted regarding the problems related to the EPC system. Following this, a series of research questions were derived, and answers were sought through expert group interviews. The problems were categorized into three headings: the EPC system and calculation problems, problems in the regulation and inspection process and, finally, the perspective on the construction industry to the EPC system is examined in the case of Turkey. Deficiencies in the rating system and calculation, regulation and inspection, and perspective of the EPC system in Turkey were identified. Suggestions for the development of EPC in Turkey were made to make it comparable with the systems in EU countries. As one of the outcomes of the study, Turkey should focus on the use of renewable energy, taking into account its geographical advantage. In addition, a more detailed micro-zoning that focuses on regional differences should be carried out, and the authorities should introduce a better control mechanism for the EPC system.
Keywords: energy performance certificate (EPC); energy efficiency; building energy demand; energy performance; renewable energy; sustainable buildings